Metabolic Health Consequences of Switching to the Bictegravir/Emtricitabine/Tenofovir Alafenamide and Dolutegravir Plus Lamivudine Regimens in Virologically Suppressed People Living with HIV Aged > 40 Years: A Retrospective Real-World Study - Shi J; Zhang W; Han J; Zhang Z; Yan D; Zheng R; Li F; Wang Y (Infection and Drug Resistance)
Jinchuan Shi,1 Wenhui Zhang,1,2 Jie Han,1,2 Zhongdong Zhang,1 Dingyan Yan,1,2 Rongrong Zheng,1 Feng Li,1 Yi Wang1,3 1Department of Infection, Affiliated Hangzhou Xixi Hospital, Zhejiang Chinese Medical University, Hangzhou, 310023, People’s Republic of China; 2Department of Nursing, Affiliated Hangzhou Xixi Hospital, Zhejiang Chinese Medical University, Hangzhou, 310023, People’s Republic of China; 3Clinical Research Laboratory, Affiliated Hangzhou Xixi Hospital, Zhejiang Chinese Medical University, Hangzhou, 310023, People’s Republic of ChinaCorrespondence: Yi Wang, Clinical Research Laboratory, Affiliated Hangzhou Xixi Hospital, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China, Email wangyi_xixi@126.comObjective: Both B/F/TAF and DTG/3TC are recommended in treatment guidelines for switch therapy in PLWH. This study aimed to evaluate the safety and metabolic health consequences of two switched regimens in a real-world setting among virologically suppressed PLWH previously treated with EFV/TDF/3TC.Methods: This retrospective real-world study in Hangzhou included 220 virologically suppressed PLWH who switched from EFV/TDF/3TC to DTG/3TC or B/F/TAF between January 1, 2020 and October 30, 2023. All participants were examined the changes in weight, BMI, GLU levels, lipid parameters (TC, LDL-C, HDL-C, and TG), and eGFR at post-12-month.Results: The mean age of included participants was 50.8 years (SD: 11.3). After 12 months of switching, the HIV RNA level was below the limit of detection (< 20 copies/mL) among all participants. The switch to DTG/3TC or B/F/TAF therapy was associated with significant improvement in LDL-C, GLU levels, and eGFR values (all P < 0.05), while other metabolic indexes did not change significantly. Furthermore, there was a significant difference in the incidence of hyperglycemia (5.7% vs 19.35%; P = 0.004) between the B/F/TAF and DTG/3TC groups, but not included the mean changes of weight, BMI, lipid profiles, GLU levels, and eGFR and incidence of high TC and high TG. For the aged 40– 59 years and aged ≥ 60 years PLWH, the differences in metabolic indicators were minimal between DTG/3TC and B/F/TAF groups post-12-month, with no significant differences between the arms in mean change from baseline in TC, TG, HDL-C, LDL-C, GLU, BMI, weight, and eGFR.Conclusion: In this study, the B/F/TAF or DTG/3TC regimens are safe for virologically suppressed PLWH aged > 40 years. The transition to B/F/TAF demonstrated dual clinical benefits, significantly reducing hyperglycemia incidence while preserving renal function.Keywords: people living with HIV, virological suppression, antiretroviral therapy, metabolic indices